Real-time polymerase chain reaction based algorithm for differential diagnosis of Kinetoplastidean species of zoonotic relevance - Muñoz-Calderón, Arturo; Wehrendt, Diana; Cura, Carolina; Gómez-Bravo, Andrea; Abril, Marcelo; Giammaria, Matilde; Lucero, Raúl Horacio; Schijman, Alejandro G. (Infection, genetics and evolution, 2020)
Kinetoplastids are a group of flagellated protozoa that infect a vast repertoire of mammals and insect vectors. From a zoonotic point of view, domestic animals are critical reservoirs for transmission of Kinetoplastidean parasites. Due to their proximity to humans, they assume substantial epidemiological importance in the context of these zoonoses and consequently in public health. Their reliable identification is relevant to understand their eco-epidemiological involvement in transmission cycles. This work aimed to develop an algorithm based on sequential Real-Time PCR (qPCR) assays targeted to different loci (24S alpha rDNA, ITS1 and Hsp70) allowing distinction among Trypanosoma cruzi, Trypanosoma rangeli, Trypanosoma evansi and Leishmania species in biological samples collected from mammalian reservoirs and triatomine vectors. The algorithm includes a first qPCR test targeted to endogenous genes conserved within mammals and within triatomine vectors as internal controls of DNA sample integrity and/or qPCR inhibition. This algorithm was evaluated in biological samples from domestic cattle (N = 14), dogs (N = 19) and triatomines (N = 19). Analytical sensitivity of 24S alpha rDNA for detection of T. rangeli was 10 fg of DNA, with a linear range between 10 fg and 10 ng. For T. cruzi it varied depending on the Discrete typing unit. The ITS1 qPCR showed an analytical sensitivity of 100 pg/reaction and 100 fg/reaction of Leishmania spp. and T. evansi DNAs. In mammal field samples, four T. cruzi 24S alpha rDNA sequences and fourteen ITS1 amplicons specific for T. evansi were detected. qPCR-HRM analysis directed to the Hsp70 gene diagnosed two dogs with Leishmania infantum infection. Among 19 triatomine field samples, T. cruzi was detected in five; T. rangeli in eight and one specimen showed a mixed infection. This diagnostic algorithm can provide more accurate records of kinetoplastidean infection burden in vectors and reservoirs, relevant to update current eco-epidemiological maps in co-endemic regions. [Display omitted] •An algorithm based on qPCR assays was developed for distinction among Kinetoplastids.•T. cruzi, T. rangeli, T. evansi and Leishmania species were detected by qPCR-HRM.•Single and mixed infections of Kinetoplastids were detected in mammalian samples.•The algorithm allowed detection of T. rangeli and T. cruzi infections in R. neglectus.•Mammalian and Triatomine genes were included as endogenous amplification controls.